Divergence of knowledge production strategies for emerging technologies between late industrialized countries: Focusing on quantum technology - Kang, Inje; Choung, Jae‐Yong; Kang, Dong‐in; Park, Inyong (ETRI journal, 2021)
Traditional wisdom on how late industrialized countries follow the technology trajectories of preceding economies is in need of reformation as these countries have attained industrial leadership in a growing number of fields. However, current understandings about these countries' development of their emerging technologies have yet to investigate the divergence of idiosyncratic technology trajectories. The aim of this paper was to explore how their knowledge production strategies in emerging technology sectors are diverging. Specifically, this research examines the changing patterns of knowledge production in quantum technology in South Korea and China by developing a knowledge portfolio and knowledge strategic diagram. According to the knowledge portfolio, the relative literature position differs. In the knowledge strategic diagram, there are diverging patterns in the emerging keywords sector. This paper contributes to the literature by demonstrating the diverging strategies of late industrialized countries in their transition from catch‐up to post‐catch‐up paradigms and provides policy implications for countries developing an idiosyncratic trajectory in emerging technology sectors.